2013
DOI: 10.1088/0004-637x/768/1/88
|View full text |Cite
|
Sign up to set email alerts
|

Late Spectral Evolution of the Ejecta and Reverse Shock in Sn 1987a

Abstract: We present observations with VLT and HST of the broad emission lines from the inner ejecta and reverse shock of SN 1987A from 1999 Feb. until 2012 Jan. (days 4381 -9100 after explosion). We detect broad lines from Hα, Hβ, Mg I], Na I, [O I], [Ca II] and a feature at ∼ 9220Å. We identify the latter line with Mg II λλ 9218, 9244, which is most likely pumped by Lyα fluorescence. Hα, and Hβ both have a centrally peaked component, extending to ∼ 4500 km s −1 and a very broad component extending to 11, 000 km s −1 ,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
64
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 60 publications
6
64
0
Order By: Relevance
“…In addition, we studied the temporal evolution of the ejecta morphology in the HST images, finding that it changes from an approximately elliptical shape before ∼5000 days to an edgebrightened, more irregular morphology thereafter. This transition coincides with and can be explained by the change in the dominant energy source powering the ejecta (from radioactive decay of 44 Ti to X-rays from the ring, see also Fransson et al 2013). …”
Section: Introductionsupporting
confidence: 57%
See 4 more Smart Citations
“…In addition, we studied the temporal evolution of the ejecta morphology in the HST images, finding that it changes from an approximately elliptical shape before ∼5000 days to an edgebrightened, more irregular morphology thereafter. This transition coincides with and can be explained by the change in the dominant energy source powering the ejecta (from radioactive decay of 44 Ti to X-rays from the ring, see also Fransson et al 2013). …”
Section: Introductionsupporting
confidence: 57%
“…Fransson et al (2013) showed that the line profile was still consistent with this blueshift at around 4400 days. This was the last optical spectrum obtained during the epoch when the energy input to the whole ejecta was dominated by radioactivity.…”
Section: Dust In the Ejectamentioning
confidence: 62%
See 3 more Smart Citations